Potensi Penularan Leptospirosis pada Petugas Rumah Pemotongan Hewan di Kota Salatiga - Aryani Pujiyanti; Dimas Bagus Wicaksono Putro; Nimas Ayu Kartikasari (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: Slaughterhouse workers have a risk of contracting leptospirosis because of daily contact with animal blood and urine. The purpose of the study was to describe the incidence of leptospirosis and measure the level of knowledge of workers and examine the relationship between demographic characteristics, the knowledge and the prevention behavior of leptospirosis.Methods: All technical staff of Slaughterhouse at Salatiga (30 people) were selected as participants. Data was collected in July 2016 through structured interviews. Microscopic Agglutination Test (MAT) was used to test the workers serum for leptospirosis. Data were analyzed using the Fisher-exact test.  Result: According to the findings, most respondents were male, between the ages of 26 and 50, and had low education background. Most respondents are unaware that leptospirosis is a serious disease and 73.3 percent of respondents had never heard of leptospirosis. The majority of participants reported negative MAT values. The majority of Slaughterhouse workers have never heard of leptospirosis and have little awareness of leptospirosis preventive methods, so they may be at risk of having the infection.Conclusion: There is no leptospirosis incidence in Slaughterhouse Salatiga, however, one worker had a history of leptospirosis exposure.There was no significant relationship between age, gender, and education level with knowledge and behavior, but the knowledge was significantly correlated with leptospirosis prevention behavior. Slaughterhouse officers are advised to receive health education about leptospirosis prevention to increase awareness of the need for self-protection in the workplace.